Effect of Low‐Temperature Torrefaction Pretreatment on the Energy–Mass Co‐Benefit of Corn Straws - Yantao Yang; Lei Song; Mei Yang; Peng Liu; Tingzhou Lei (Energy Science & Engineering)
ABSTRACT To explore the effects of low‐temperature torrefaction on physicochemical properties and energy–mass co‐benefit of corn straws, the products obtained after torrefaction at different low temperatures were studied. Through proximate analysis, ultimate analysis, scanning electron microscopy, and higher calorific value, the effects of different low‐temperature torrefaction on physicochemical properties of corn straws and energy–mass co‐benefit were studied. The results showed as follows: After low‐temperature torrefaction pretreatment, with the decrease of volatile matter, the H/C ratio decreased by 21.59%, the O/C ratio decreased by 19.05%, and the higher calorific value increased by 14.78% from 19.42 to 22.29 MJ·kg−1. Therefore, low‐temperature torrefaction pretreatment can promote the volatilization of light components in corn straws, significantly increase the fixed carbon content, and then improve the mass density and energy quality into high‐grade fuels. The improvement of mass density is convenient for storage and transportation, and the improvement of energy–mass is convenient for improving the calorific value of combustion.